Alkaloid screening of Annona emarginata (Schltdl.) H. Rainer rootstocks to increase fungal tolerance in Annona atemoya Mabb. crops revealed by MS and NMR chemical profiling - da Silva, Gustavo Cabral [UNESP]; Dutra, Lívia Macedo; da Silva Almeida, Jackson Roberto Guedes; da Silva, Felipe Moura Araujo; Harakava, Ricardo; Honório, Ana Beatriz Marques [UNESP]; de-la-Cruz-Chacón, Ivan; Martínez-Vázquez, Mariano; Ferreira, Gisela [UNESP] (Elsevier, 2024)
Annona atemoya Mabb. (atemoya) is a species of the Annonaceae family that presents high commercial value in Brazil for its edible fruit. However, A. atemoya production is highly prone to field losses due to high susceptibility to fungal diseases such as anthracnose. Alternatively, the use of Annona emarginata (Schltdl.) H. Rainer rootstocks has been pointed as a possible strategy to reduce losses resulting from fungal attack, being this species a promising source of antifungal alkaloids, such as liriodenine. Therefore, the objective this study was to determinate the alkaloid profiling of A. emarginata accessions ('terra-fria' morphotype) in roots from adults and young plants and to determinate their antifungal activity which will lead to the establishment of its potential use as rootstock to A. atemoya. The hypothesis is that the roots of A. emarginata have a diversity of antifungal alkaloids that supports its use as a rootstock. Thus, in order to identify potential rootstocks tolerant to anthracnose, adult (A1–A9) and young (Y1–Y9) A. emarginata plants were investigated for their total alkaloid content (TAC), alkaloid profile by MS and NMR analysis, and antifungal activity against Colletotrichum fructicola and Colletotrichum theobromicola. In addition, multivariate analyses were performed based on MS data. Also, atemoya plants grafted onto A. emarginata (AC) were studied to determine the differences in relation to A. emarginata without grafting. Regarding TAC, the variation among adults was 29.282 – 276.774 µg g−1, and among young plants, variation was 18.633–76.739 µg g−1. Eight alkaloids were identified using a profiling approach based on NMR and MS analysis, named reticuline (1), anonaine (2), liriodenine (3), asimilobine (4), nornuciferine (5), xylopine (6), lysicamine (7), and oxoxylopine (8). Compounds 5, 7 and 8 are being described for the first time in A. emarginata. The multivariate analysis based on MS profile pointed 1 as the main chemical marker to adult A. emarginata samples and to atemoya grafted onto A. emarginata (AC), while 2 and 3 were remarkable among young A. emarginata plants. Regarding the antifungal potential, young and adult plants showed inhibition for both fungi, samples A6, A9, Y2, and Y4 presented the best activity against C. fructicola (17.7, 24.1, 26.1 and 24.7% inhibition with respect to control). Samples A2, A9, Y2 and Y4 presented the highest antifungal potency against C. theobromicola (35.4, 68.3, 68.1 and 83.5% inhibition with respect to control). AC was active against C. fructicola (18.3% inhibition) and against C. theobromicola (11.3% inhibition). Liriodenine was more active against C. fructicola (19.1% inhibition) than C. theobromicola (7.6% inhibition). These results corroborate the use of A. emarginata as rootstocks due the presence of antifungal alkaloids, including the first report of alkaloids 5, 7 and 8 and highlights some A. emarginata accessions as promising rootstocks due the tolerance against two important anthracnose-related fungi.
Keywords: Alkaloid antifungal; Annona atemoya-rootstock; Annonaceae; MS profiling; NMR profiling